Doctors training in physiology Laboratory - Iqbal, Tehseen Iqbal (Pakistan Journal of Physiology, 2019)
Practical physiology laboratory is to provide the students with necessary practical understanding of physiological principles that will enable them to become good practicing physicians. In Pakistan, laboratory curriculum of Medical Physiology has been updated extensively. Experiments using animals have been replaced by the experiments based on clinical examination of normal, healthy, human subjects. Physiology teachers integrate pre-medical subjects with the basic medical sciences and then to clinical sciences and ultimately to the professional practice. Student learns basic manual skills when he palpates arterial pulses and learns clinical skills of palpation and percussion. After that he learns to use some instruments on normal, healthy, human beings and then on the patients. Finally, the student is taught medical ethics of dealing with human beings. Laboratory curriculum should be revised after every few years to include the latest medical equipment and therapeutic techniques. Medical student is meticulously trained before handling the patients. Pak J Physiol 2019;15(3):1–2